2018
DOI: 10.1119/1.5051181
|View full text |Cite
|
Sign up to set email alerts
|

Airy wavepackets are Perelomov coherent states

Abstract: Accelerating non-spreading wavepackets in nonrelativistic free particle system, with probability distribution having an Airy function profile, were discovered by Berry and Balazs (1979), and have been subsequently realised in several optical experiments. It is shown that these wavepackets are actually Perelomov coherent states. It is found that the Galilean invariance of the Schrödinger equation plays a key role in making these states unique and giving rise to their unusual propagation properties.a This paper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the realm of QED, which describes the radiationmatter interaction with unprecedented precision, and nonlinear optics, many phenomena can be modeled by a driven time-dependent HO. In fact, it can be shown that a HO, initially in its fundamental state which is acted by an external time-dependent force, is necessarily brought into a coherent state [6][7][8][9][10]. The counterpart of this result in quantum optics is the fact that any classical current coupled to the radiation field gives rise to a coherent state of the (quantized) electromagnetic field [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of QED, which describes the radiationmatter interaction with unprecedented precision, and nonlinear optics, many phenomena can be modeled by a driven time-dependent HO. In fact, it can be shown that a HO, initially in its fundamental state which is acted by an external time-dependent force, is necessarily brought into a coherent state [6][7][8][9][10]. The counterpart of this result in quantum optics is the fact that any classical current coupled to the radiation field gives rise to a coherent state of the (quantized) electromagnetic field [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost half of a century ago it was shown [1] that there existed a specific solution of that equation expressed in the Airy function which on the one hand did not change its form (that is why it is called a coherent state), and on the other hand, it demonstrated an accelerating motion. This exotic solutions have recently aroused some interest [2] in possible applications of the description of non-spreading optical beams [3] and the generation and control of plasma in dielectrics [4].…”
Section: Introductionmentioning
confidence: 99%
“…These novel wave packets contain boundless energy and a distinct self-focusing property. Researchers were encouraged by Berry and Balazs' discovery to expand theoretical investigations on similar waves [4][5][6]. Three decades after their theoretical prediction, an experimental observation of a shortened Airy wave packet was made in optics, where the paraxial equation of diffraction and the Schrödinger equation are identical [7][8][9][10][11][12].…”
mentioning
confidence: 99%